1988
DOI: 10.1002/bbpc.198800035
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport in Molten Salt Rich Na — NaX Solutions (X = Br, I)

Abstract: Electrical Properties / Electrochemistry / Liquids / Metal-Nonmetal Transition / Thermodynamics The electronic conductivity of liquid Na -NaI and Na -NaBr has been measured over a wide concentration range from dilute to conce.ntr~ted non':'1etaIlic solutions at different temperatures between 700 and 900°C. Two methods have been applied, the Wagner lar.lzatlOn techniqueat low metal activitiesand an ac-techniqueat high activitieswherethe concentration has been varied bycoulometric tltrat~on. A thermodyn~mlc defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, its solubility does not exceed 1 mol% and remains low compared to other alkali metals in solution their metal halide (up to 10 mol% for Na in NaBr). Haarberg et al [98,99] studied the electronic conduction in Na halide melts. However, they used Bi electrodes and it has been shown that Na-Bi alloys exhibit solubility of Bi as well as Na in molten salts due to Bi 3− formation [100].…”
Section: Solubility Of Lithium and Electronic Conductivitymentioning
confidence: 99%
“…However, its solubility does not exceed 1 mol% and remains low compared to other alkali metals in solution their metal halide (up to 10 mol% for Na in NaBr). Haarberg et al [98,99] studied the electronic conduction in Na halide melts. However, they used Bi electrodes and it has been shown that Na-Bi alloys exhibit solubility of Bi as well as Na in molten salts due to Bi 3− formation [100].…”
Section: Solubility Of Lithium and Electronic Conductivitymentioning
confidence: 99%
“…New investigations of alternative sodium itinerant electrolytes must not only be aware of this detrimental tendency but will also need to quantify the solubility of sodium metal via techniques similar to Bredig's and electronic conductivity contributions via polarization methods as developed by Wagner [94] and employed by Haarberg et al [95,96]. Current miscibility mitigation strategies [97] include (i) the use of mixtures of molten salts to decrease solubility, (ii) the operation of the device at lower temperatures, and (iii) further separation of the anode and cathode compartments to reduce the rate of back reaction.…”
Section: Corrosion Mechanismsmentioning
confidence: 99%
“…On the other hand, formation of alkali metals or eu ropium solutions results in the appearance of elec tronic conductivity in the melt, which brings about the shift of the electrochemical interface into the bulk of the melt. Probably this shift is quite large, because the diffusion coefficients of alkali metals have values of 10-3 -10-2 cm2s-1 [33], that is at least two or ders of magnitude higher than diffusion coefficients of europium ions. So the process of electroreduction occurs not only on the surface substrate, but in the bulk of the melt also.…”
Section: Cyclic Voltammetry Of the Process Eu(ii) + 2e~ O Eumentioning
confidence: 99%
“…Related with this is the fact that a redox electrochemical reaction usually is a reversible process (even at high polariza tion rates up 5-10 Vs-1 ) [38], because these reactions can in principle occur only with a change of charge and without a change in the composition of the com plexes. The sluggish kinetics of the reaction EuC163~ + e~ -► Eu2+ + 6C r (33) is connected with substantial rearrangement of the eu ropium coordination sphere (probably the loss of six ligands) which occurs during the electrode reaction.…”
Section: Peculiarity Of Intervalence Charge Transfer Of the Couple Eumentioning
confidence: 99%